Association between cystine urolithiasis and neuter status of dogs within the UK. (5th July 2017) - Florey, J.; Ewen, V.; Syme, H.
Abstract : Objectives: The objectives of the study were to examine the association between diagnosis of cystine urolithiasis and entire versus neutered status in male dogs and whether the strength of association varies among breeds. Materials and Methods: A previously reported canine urolithiasis database was used, documenting all urolith submissions to Hill's Pet Nutrition UK over a 10‐year period. Uroliths were classified as cystine or non‐cystine, and only male dogs with known neuter status were included in the analysis. Breeds of dog (and an additional crossbreed group), for which there was a minimum of 10 cystine urolith submissions, were analysed individually, with all other breeds combined together to form a reference group. Results were analysed using chi‐squared and Fisher's exact tests. Logistic regression was used to assess associations between breed and neuter status and formation of cystine calculi. Results: In multiple breeds, dogs with cystine uroliths were significantly more likely to be entire than dogs forming other types of urolith. Being an entire male, regardless of breed, was associated with an increased risk of cystine urolithiasis (odds ratio=4·5; 95% confidence interval: 3·22 to 6·37; P<0·001). Clinical Significance: Increased odds of cystine formation in entire dogs supports further investigation of castration as a method to prevent cystine urolithiasis.